(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Gardenia gummifera L. f is a rarely explored medicinal plant species found in the dry forests of Karnataka, Tamil Nadu, Andhra Pradesh, and Kerala. The present work evaluates the anti-proliferative effect of the root bark of G. gummifera on HepG2 cell lines. With standard protocols, qualitative and quantitative phytochemical analysis of petroleum ether, chloroform, acetone, ethanol, and aqueous extracts were carried out. The acetone, ethanol, and aqueous extracts from the root bark of G. gummifera were subjected to antioxidant assays. The anti-proliferative assays such as methyl tetrazolium (MTT) assay, Neutral red assay, and lactate dehydrogenase (LDH) leakage were performed on HepG2 cell lines. The phytochemical examination indicated the presence of primary and secondary metabolites, especially polyphenolic compounds. Among the different extracts, acetone, ethanol, and aqueous extracts exhibited maximum availability of flavonoids and tannins. Also, ethanol extract exhibited the highest free radical scavenging potential with the lowest IC50. Between the different extracts, the highest cytotoxic activity was observed in the ethanol extract of G. gummifera. Hence, this work highlights the significance of ethanol extract of G. gummifera L. f as a potent anti-cancer agent for clinical use in the battle against liver cancer.